Incidental Detection of a Rare Pediatric High-Grade Fibrosarcoma in a Post-traumatic Setting: The Conundrum of Intra-Abdominal Hematoma versus Neoplasia - Kamand Khalaj; Nikoo Fattahi; Allen C. Omo-Ogboi; Jaiyeola O. Thomas-Ogunniyi; Olanrewaju A. Ogunleye; Ashish Khanal; Larry A. Kramer (Case Reports in Radiology)
Infantile fibrosarcoma (IF) is a rare malignant fibroblastic tumor that affects infants and young children, occurring most commonly in the extremities. Here, we present a 14-year-old patient with an abdominal mass incidentally detected after a blunt injury to the abdomen. The initial trauma protocol CT revealed a high attenuation mesenteric lesion in the left central abdomen suggestive of mesenteric hematoma. However, the possibility of a solid neoplastic mass lesion could not be excluded. Further evaluation with dynamic contrast-enhanced serial MRI showed a progressive enhancing mass and excluded a hyperacute hematoma with active bleeding. The mass was resected, and histopathological examination and molecular analysis of tumor cells were consistent with a high-grade fibrosarcoma with KMT2D : BCOR fusion.